Absorption and Fluorescence Properties of 3,6-bis(5-bromothiophen-2-yl)-2,5-bis(2-ethylhexyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione. A Covalent Fluorescence in Solution and in the Solid State (Baghdad Science Journal, 2022)
In the cuurent article, the photophysical properties of 3,6-bis(5-bromothiophen-2-yl)-2,5-bis(2-ethylhexyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione were investigated. The visible absorption bands at 527, 558 and 362 nm in propylene carbonate and the compound was found to be fluorescent in solution and in the plastic film with emission wavelengths between 550- 750 nm. The Stokes Shift of P.C., acetonitrile, diethyl ether, Tetrahydrofuran THF, cyclohexane, dibutyl ether, and dichloromethane DCM  are 734, 836, 668, 601, 601, 719, and 804 cm-1 in respectively. The Stokes Shift Δ was less in THF and cyclohexane, than the solvents, which indicates that the energy loss is less between the excitation and fluorescence states. The photophysical characterizations were carried out on the compound in different solvents, the compound displays 12 nm red-shift in the absorption maximum in toluene compared with in propylene carbonate P.C, which the λmax was 558 nm in P.C. The compound displays 5 and 10 red-shifts in the absorption maximum in diethyl ether and dibutyl ether respectively. The absorption band is almost insensitive to the polarity of the solvent, showing only a slight red shift from 563 nm in diethyl ether to 569 nm in cyclohexane  and also red shift from 558 nm in acetonitrile to 570 nm in toluene , which appreciably red-shifted depending on the polarity of the solvent. The emission maxima of the dye slightly shift more red region, such as DCM and toluene when compared this compound in other solvents. The dye showed a slight red shift ca. 5 nm on moving from the acetonitrile to the less polar solvent, such as dichloromethane DCM.